2017
DOI: 10.1016/j.jfda.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm activity of cashew juice pulp against Staphylococcus aureus , high performance liquid chromatography/diode array detection and gas chromatography-mass spectrometry analyses, and interference on antimicrobial drugs

Abstract: The epidemiology of Staphylococcus aureus infections has evolved in recent years, as this species is a major Gram-positive pathogen associated with healthcare services. The antimicrobial resistance of this species raises an urgent need for new treatment strategies. Fruits play important nutritional and economic roles in society, but their biological and pharmacological features are poorly explored when compared to nonedible parts of plants such as barks and leaves. In this study, we show that the cashew apple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…Although clinical isolates were used in this study, our sample is limited to 10 strains of each species; thus, researches with larger samples are important to confirm our observations [40]. Despite the antimicrobials used in this study are highly relevant in clinical treatments of infectious diseases, it would be of interest to conduct the assays with a larger number of drugs from different pharmacological groups, in order to explore the combined used of DEXA with drugs of distinct mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical isolates were used in this study, our sample is limited to 10 strains of each species; thus, researches with larger samples are important to confirm our observations [40]. Despite the antimicrobials used in this study are highly relevant in clinical treatments of infectious diseases, it would be of interest to conduct the assays with a larger number of drugs from different pharmacological groups, in order to explore the combined used of DEXA with drugs of distinct mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the chemical changes. The previous study demonstrated that the presence of polyphenols may have contributed to this result, as many molecules of this chemical group can appear antimicrobial activity [27]. In the investigation of the FDS of C. carandas demonstrated the antimicrobial activity against the 10 tested microorganisms, showed that C. carandas was the potential antibacterial agent.…”
Section: Toobpeng Et Almentioning
confidence: 92%
“…For CBE-F, a higher concentration was required to obtain a complete inhibition of the L. monocytogenes and S. aureus bacteria, with MIC values of 8.300 µg mL -1 (Table 6). Dias-Souza et al (2017) reported that the extract of pulp cashew presented inhibitory and bactericidal effects against Staphylococcus aureus strains at 15.60 and 125 µg mL -1 respectively; and HPLC analysis confirmed the presence of polyphenols associated with antimicrobial activity.…”
Section: Antimicrobial Effect Of Cashew Apple Coproduct Extractsmentioning
confidence: 93%